Encyclopedia of football medicine. - Meyer, Tim (Thieme clinical collection., 2017)
Volume 3 covers a range of multidisciplinary topics that aim to ensure that players can compete safely and maintain peak fitness and performance, while preventing disabling injuries insofar as possible. -- Publisher.